Agenda setting diaspora: a comparative analysis of news article coverage on BERSIH 3.0 by keadilandaily.com and umnoonline.com - Selamat, Muhamad Rosli; Rosli, Muhamad Ridhwan (Center for Enhancing Knowledge, 2015)
The increase use of the new media as an alternative media in the landscape of Malaysia's politics have open up spaces and chances to examine the adoption of agenda setting theory by the online newspaper owners. The rally of BERSIH 3.0 which took place on the 28th April 2012 organised by the Coalition for Clean and Fair Elections (BERSIH), was seen not only as a rally to demand for a clean and fair election in Malaysia, but was also seen as a political move by the opposition parties in wooing the support of the Malaysian public towards their establishment and advancing their agenda setting diaspora through new media channel which is claimed to be free and non-partisan by the authority. This study is attempting to identify the orientation of agenda setting diaspora (construct) by two websites in disseminating their messages on BERSIH 3.0. The two websites of www.keadilandaily.com and www.umnoonline.com were selected for the study as the former owned by the main opposition party (Parti Keadilan Rakyat - PKR) and, the later owned by a dominating ruling party (United Malays National Organization - UMNO). A total of 124 news articles on BERSIH 3.0 published by keadilandaily.com and umnoonline.com for fifteen days starting from 21stApril 2012 to 5th May 2012 (one week before and one week after BERSIH 3.0 rally) were analysed. Out of 124 news articles, 77 were published by keadilandaily.com and another 47 news articles were published by umnoonline.com. The results indicated that firstly, the positive portrayal of theme credibility of BERSIH 3.0 is significantly delivered more by keadilandaily.com as compared to umnoonline.com. Secondly, the neutral portrayal of theme credibility of BERSIH 3.0 is significantly disseminated more by keadilandaily.com as compared to umnoonline.com. And finally, the negative portrayal of theme credibility of BERSIH 3.0 is significantly adopted more by umnoonline.com as compared to keadilandaily. com. These results noted that the orientations and the reflections of agenda setting constructs by the two news websites of www.keadilandaily.com and www. umnoonline.com on the coverage of BERSIH 3.0 rally is contradictory in nature, as keadilandaily.com adopted a more balanced and justified approach by having objective and proactive presentation of theme portrayal for the majority of its news articles. While, umnoonline.com is adopting a more conservative and stereotype-approach presentation by having more negative portrayal of theme on its news articles on BERSIH 3.0.